Blogs, webinars and significant learning: A case report on a teacher training program for college teachers - Rodrigo Polanco-Bueno (Laureate Education Inc, 2013)
This case study reports on a teacher training experience for college professors in which participants were trained, taking advantage of technological tools, in two main teaching competences. First, professors were trained to use technology to enrich students' learning outcomes. Second, they applied strategies of significant learning in the design of students' learning experiences. The learning experience consisted in an International Certificate on Significant Learning integrated by six modules, 20 hours each. Every module of the program consisted of two consecutive webinars with online activities in between. The results showed the positive impact of the program on participants' perceptions about the quality of the contents, evidence of learning and products (E-portfolios) that served as content mastery evidences, as well as learning products produced by their students. DOI: 10.18870/hlrc.v3i1.72